Improvement of Short Story Writing with Synectic Models and Creative Models - Productive Materials of Literature Creativity Department of Indonesian Language and Literature Education 8Th Semester FKIP UMSU - Amnur Rifai Dwirsyah (Budapest International Research and Critics University, 2020)
Writing short stories is often felt to be a difficult and difficult thing, especially for novice writers, including college students who write creative writing. Students have difficulty when given the task of writing short stories. The short stories that they produce are mostly of poor quality marked by the expression of themes into the short, unified and in-depth elements of the short stories. It shows that they do not understand and master the themes (things) that they adopt as short stories.The problem raised in this research is whether lectures with the developed synectic model can improve student skills in writing short stories. The subjects of this study were students of the S1 Indonesian Language and Literature Education Study Program. The design of this study was designed based on classroom action research through two research cycles. Each cycle consists of planning, action, observation, reflection, and evaluation. Data collection is done through tests, observations, interviews, and journals. Data analysis was carried out quantitatively and qualitatively. The results showed that the developed synectic learning model Learning with the developed synectic model proved to be able to improve the quality of student learning outcomes, namely short story writing skills which include indicators (1) content, (2) organization, (3) vocabulary, (4) languages and (5) mechanics. The improvement in the quality of student learning outcomes is evident from the increase in the average pre-action score of 64.10 in the less category, in the first cycle of 69 sufficient categories, and in the second cycle 78.23 in the moderate category. Learning with the developed synectic model turns out to be able to change student learning behavior from negative to positive.